INTERNATIONAL COURT OF JUSTICE, CASE CONCERNING THE DISPUTE REGARDING NAVIGATIONAL AND RELATED RIGHTS (COSTA RICA V NICARAGUA) JUDGMENT OF 13 JULY 2009 - Bjorge, E (2011)
The technique of 'evolutive interpretation' is well known in public international law.2 It is particularly associated with treaty regimes like that of the European Convention on Human Rights (ECHR).3 The currency of this technique of interpretation has, however, been less evident in general public international law. It is not insignificant therefore that the International Court of Justice (ICJ), in a case about navigational and related rights has now made unambiguously clear that, where the parties have used generic terms in a treaty, aware that the meaning of the terms was likely to evolve over time, and where the treaty is one of continuing duration, the parties as a general rule must be presumed to have intended those terms to have an 'evolving meaning'.4 © Copyright 2011 British Institute of International and Comparative Law.